Brain somatic mutations in MTOR cause focal cortical dysplasia type II leading to intractable epilepsy - Lim, Jae Seok; Kim, Woo-il; Kang, Hoon-Chul; Kim, Se Hoon; Park, Ah Hyung; Park, Eun Kyung; Cho, Young-Wook; Kim, Sangwoo; Kim, Ho Min; Kim, Jeong A; Kim, Junho; Rhee, Hwanseok; et al. (Nature medicine, 2015)
Deep sequencing identifies somatic activating mutations of MTOR in affected brain regions of FCDII patients that are sufficient to cause neuronal migration defects and epileptic seizures in mice. Focal cortical dysplasia type II (FCDII) is a sporadic developmental malformation of the cerebral cortex characterized by dysmorphic neurons, dyslamination and medically refractory epilepsy 1 , 2 . It has been hypothesized that FCD is caused by somatic mutations in affected regions 3 , 4 . Here, we used deep whole-exome sequencing (read depth, 412–668×) validated by site-specific amplicon sequencing (100–347,499×) in paired brain-blood DNA from four subjects with FCDII and uncovered a de novo brain somatic mutation, mechanistic target of rapamycin ( MTOR) c.7280T>C (p.Leu2427Pro) in two subjects. Deep sequencing of the MTOR gene in an additional 73 subjects with FCDII using hybrid capture and PCR amplicon sequencing identified eight different somatic missense mutations found in multiple brain tissue samples of ten subjects. The identified mutations accounted for 15.6% of all subjects with FCDII studied (12 of 77). The identified mutations induced the hyperactivation of mTOR kinase. Focal cortical expression of mutant MTOR by in utero electroporation in mice was sufficient to disrupt neuronal migration and cause spontaneous seizures and cytomegalic neurons. Inhibition of mTOR with rapamycin suppressed cytomegalic neurons and epileptic seizures. This study provides, to our knowledge, the first evidence that brain somatic activating mutations in MTOR cause FCD and identifies mTOR as a treatment target for intractable epilepsy in FCD.